2013
DOI: 10.3390/cancers5041577
|View full text |Cite
|
Sign up to set email alerts
|

Surrogates of Long-Term Vitamin D Exposure and Ovarian Cancer Risk in Two Prospective Cohort Studies

Abstract: Experimental evidence and ecologic studies suggest a protective role of vitamin D in ovarian carcinogenesis. However, epidemiologic studies using individual level data have been inconsistent. We evaluated ultraviolet (UV)-B radiation, vitamin D intake, and predicted plasma 25-hydroxyvitamin D [25(OH)D] levels as long-term surrogates of vitamin D exposure within the Nurses’ Health Study (NHS) and NHSII. We estimated incidence rate ratios (RRs) and 95% confidence intervals (CIs) for risk of overall ovarian cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…However, epidemiological evidence that vitamin D status influences OC risk is inconsistent. One systemic review concluded that there is no strong evidence that vitamin D decreases risk 260 and a meta-analysis of ten longitudinal studies 261 as well as other cohort studies 262 reached a similar conclusion. In the meta-analysis the protective effect was evident in seven of the ten studies and the pooled estimate was a 17% reduced risk with increasing 25(OH)D levels; however, the pooled estimate was not statistically significant (RR = 0.83, 95% CI: 0.63–1.08) 261 .…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 99%
“…However, epidemiological evidence that vitamin D status influences OC risk is inconsistent. One systemic review concluded that there is no strong evidence that vitamin D decreases risk 260 and a meta-analysis of ten longitudinal studies 261 as well as other cohort studies 262 reached a similar conclusion. In the meta-analysis the protective effect was evident in seven of the ten studies and the pooled estimate was a 17% reduced risk with increasing 25(OH)D levels; however, the pooled estimate was not statistically significant (RR = 0.83, 95% CI: 0.63–1.08) 261 .…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 99%
“…5 Several recent studies have examined whether or not serum 25-hydroxyvitamin D [25(OH)D] concentrations are associated with ovarian cancer risk or mortality. [6][7][8][9][10][11][12] Vitamin D is produced in the skin when 7-dehydrocholesterol is exposed to Ultraviolet B. It is transported to the liver, where it is hydroxylated to become 25(OH)D. It then undergoes a second hydroxylation step, primarily in the liver, to become the active form, 1,25-dihydroxyvitamin D (calcitriol).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 350 independent articles on ovarian cancer incidences were found, among which 93 were judged to be eligible for full-text review (Figure 1). Seventeen articles met our inclusion criteria [14,[27][28][29][30][31][32][38][39][40][41][42][43][44][45][46][47], of which nine had been included in a previous systematic review [13] and four in a previous meta-analysis [15]. Two articles reported the results of pooled analyses [14,41], which included some individual studies on vitamin D exposure and ovarian cancer that had not been previously published.…”
Section: Study Selectionmentioning
confidence: 99%
“…Two articles reported the results of pooled analyses [14,41], which included some individual studies on vitamin D exposure and ovarian cancer that had not been previously published. Of the 17 eligible studies, vitamin D was assessed according to sun exposure in four studies [27][28][29]31], dietary intake in 10 studies [28][29][30][39][40][41][42][43][44][45] and circulating 25(OH)D levels in five studies [14,32,38,46,47]. For ovarian cancer survival, a total of 281 independent articles were found, of which 47 were judged to be eligible for full-text review and three were retained ( Figure 2) [33][34][35].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation